Desain Strategi dan Assessment Kesiapan Redenominasi di Indonesia - Eko Sumando; M. Hatta Hasanuddin (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2017)
The relevance of redenomination policy are being revisited, especially to address the implementation of the Asean Economic Community (AEC). The main reason is, redenomination will improve the efficiency of business transactions and the Indonesian economy, which in turn can be a competitive advantage in the open trade zone era. This study will contributes to the gap in the strategic design for change management and assessment for the community readiness for redenomination implementation. The strategies that are offered in this study, are: (1) Assessment of public understanding of redenomination; (2) Options/ diversification of the communication media; (3) The use of electronic cash as a means of efficiency than printing new money; and (4) Rounding strategy. Abstrak Kebijakan Redenominasi kembali diuji relevansinya, khususnya dalam menyikapi pelaksanaan Masyarakat Ekonomi Asean (MEA). Alasan utamanya, Redenominasi, akan meningkatkan efisiensi transaksi bisnis dan perekonomian Indonesia, yang pada akhirnya dapat menjadi competitive advantage pada era zona perdagangan terbuka. Kajian ini akan menjembatani gap yang ada dalam desain strategi manajemen perubahan dan assesment kesiapan masyarakat dalam implementasi Redenominasi. Strategi yang ditawarkan dalam studi ini, yaitu: (1) Assessment pemahaman masyarakat terhadap Redenominasi; (2) Pilihan/diversifikasi media komunikasi kebijakan; (3) Penggunaan electronic cash sebagai sarana efisiensi pencetakan uang baru; dan (4) Strategi pembulatan.